A Novel C Type CpG Oligodeoxynucleotide Exhibits Immunostimulatory Activity In Vitro and Enhances Antitumor Effect In Vivo - Li, Tete; Wu, Jing; Zhu, Shan; Zang, Guoxia; Li, Shuang; Lv, Xinping; Yue, Wenjun; Qiao, Yuan; Cui, Jiuwei; Shao, Yan; Zhang, Jun; Liu, Yong-Jun; et al. (Frontiers in Pharmacology, 2020)
Background: C type CpG oligodeoxynucleotides (CpG-C ODNs), possessing the features of both A type and B type CpG ODNs, exert a variety of immunostimulatory activities and have been demonstrated as an effective antitumor immunotherapy. Based on the structural characteristics, we designed 20 potential ODNs with the aim of synthesizing an optimal, novel CpG-C ODN specific to human and murine Toll-like receptor 9 (TLR9). We also sought to investigate the in vitro immunostimulatory and in vivo antitumor effects of the novel CpG-C ODN. Methods: Twenty potential CpG-C ODNs were screened for their ability to secrete interferon (IFN)-α, and interleukin (IL)-6 and tumor necrosis factor (TNF)-α production for the three most promising sequences were assayed in human peripheral blood mononuclear cells (PBMCs) by enzyme-linked immunosorbent assay (ELISA) or cytometric bead array assay. The functions of human and mouse B cells, and cytokine production in mice induced by the most promising sequence, HP06T07, were determined by flow cytometry and ELISA. Growth and morphology of tumor tissues in in vivo murine models inoculated with CT26 cells were analyzed by a growth inhibition assay and immunohistochemistry, respectively. Results: Among the 20 designed ODNs, HP06T07 significantly induced IFN-α, IL-6 and TNF-α secretion, and promoted B-cell activation and proliferation in a dose-dependent manner in human PBMCs and mouse splenocytes in vitro. Intratumoral injection of HP06T07 notably suppressed tumor growth and prolonged survival in the CT26 subcutaneous mouse model in a dose-dependent manner. HP06T07 administered nine times at 2-day intervals (I2) eradicated tumor growth at both primary and distant sites of CT26 tumors. HP06T07 restrained tumor growth by increasing the infiltration of T cells, NK cells and plasmacytoid dendritic cells (pDCs). Conclusions: HP06T07, a novel CpG-C ODN, shows potent immunostimulatory activity in vitro and suppresses tumor growth in the CT26 subcutaneous mouse model.